Childhood intussusception: The implications of delayed presentation - Ekenze S; Mgbor S (Wolters Kluwer Medknow Publications, 2011)
Background : In some developing countries, many children with intussusception are reported to present late for definitive therapy. This study determines the effect of delayed presentation on clinical parameters, management, and outcome of childhood intussusception in southeast Nigeria. Methods : Comparative analysis of 87 consecutive children with intussusception managed from January 1998 to December 2007 at the University of Nigeria Teaching Hospital, Enugu, was done. Results : Overall, the mean time from onset to presentation was 3.0 days (range 4 hours to 7 days). Thirteen (14.9%) presented within 24 hours of symptoms (group 1) and 74 (85.1%) presented after 24 hours (group 2). Clinical presentations were similar in the children with the exception of bilious vomiting, rectal bleeding, and abdominal distension which were significantly commoner in group 2 children (P < 0.05). Type of intussusception found at operation did not differ in the groups, but cases in group 2 had higher incidence of bowel complications, and greater risk of failed operative reduction and bowel resection than group 1 patients (P < 0.05). Though the postoperative complications did not differ significantly between the two groups, mortality directly related to intussusception occurred only in patients who presented after 24 hours. Conclusion: Significant number of children with intussusception in our setting presented late for definitive treatment. These cases have a higher risk of bowel complications and intestinal resection. Outcome in these patients might be enhanced through improved perioperative care in the short term, or by improving access to, and reducing delays in seeking health care, in the long run.